Pathogen-reduced platelets for the prevention of bleeding. - Butler, C; Doree, C; Estcourt, L; Trivella, M; Hopewell, S; Brunskill, S; Stanworth, S; Murphy, M (2013)
BACKGROUND: Platelet transfusions are used to prevent and treat bleeding in patients who are thrombocytopenic. Despite improvements in donor screening and laboratory testing, a small risk of viral, bacterial or protozoal contamination of platelets remains. There is also an ongoing risk from newly emerging blood transfusion-transmitted infections (TTIs) for which laboratory tests may not be available at the time of initial outbreak.One solution to reduce further the risk of TTIs from platelet transfusion is photochemical pathogen reduction, a process by which pathogens are either inactivated or significantly depleted in number, thereby reducing the chance of transmission. This process might offer additional benefits, including platelet shelf-life extension, and negate the requirement for gamma-irradiation of platelets. Although current pathogen-reduction technologies have been proven significantly to reduce pathogen load in platelet concentrates, a number of published clinical studies have raised concerns about the effectiveness of pathogen-reduced platelets for post-transfusion platelet recovery and the prevention of bleeding when compared with standard platelets. OBJECTIVES: To assess the effectiveness of pathogen-reduced platelets for the prevention of bleeding in patients requiring platelet transfusions. SEARCH METHODS: We searched the Cochrane Central Register of Controlled Trials (CENTRAL, The Cochrane Library 2013, Issue 1), MEDLINE (1950 to 18 February 2013), EMBASE (1980 to 18 February 2013), CINAHL (1982 to 18 February 2013) and the Transfusion Evidence Library (1980 to 18 February 2013). We also searched several international and ongoing trial databases and citation-tracked relevant reference lists. We requested information on possible unpublished trials from known investigators in the field. SELECTION CRITERIA: We included randomised controlled trials (RCTs) comparing the transfusion of pathogen-reduced platelets with standard platelets. We did not identify any RCTs which compared the transfusion of one type of pathogen-reduced platelets with another. DATA COLLECTION AND ANALYSIS: One author screened all references, excluding duplicates and those clearly irrelevant. Two authors then screened the remaining references, confirmed eligibility, extracted data and analysed trial quality independently. We requested and obtained a significant amount of missing data from trial authors. We performed meta-analyses where appropriate using the fixed-effect model for risk ratios (RR) or mean differences (MD), with 95% confidence intervals (95% CI), and used the I² statistic to explore heterogeneity, employing the random-effects model when I² was greater than 30%. MAIN RESULTS: We included 10 trials comparing pathogen-reduced platelets with standard platelets. Nine trials assessed Intercept® pathogen-reduced platelets and one trial Mirasol® pathogen-reduced platelets. Two were randomised cross-over trials and the remaining eight were parallel-group RCTs. In total, 1422 participants were available for analysis across the 10 trials, of which 675 participants received Intercept® and 56 Mirasol® platelet transfusions. Four trials assessed the response to a single study platelet transfusion (all Intercept®) and six to multiple study transfusions (Intercept® (N = 5), Mirasol® (N = 1)) compared with standard platelets.We found the trials to be generally at low risk of bias but heterogeneous regarding the nature of the interventions (platelet preparation), protocols for platelet transfusion, definitions of outcomes, methods of outcome assessment and duration of follow-up.Our primary outcomes were mortality, 'any bleeding', 'clinically significant bleeding' and 'severe bleeding', and were grouped by duration of follow-up: short (up to 48 hours), medium (48 hours to seven days) or long (more than seven days). Meta-analysis of data from five trials of multiple platelet transfusions reporting 'any bleeding' over a long follow-up period found an increase in bleeding in those receiving pathogen-reduced platelets compared with standard platelets using the fixed-effect model (RR 1.09, 95% CI 1.02 to 1.15, I² = 59%); however, this meta-analysis showed no difference between treatment arms when using the random-effects model (RR 1.14, 95% CI 0.93 to 1.38).There was no evidence of a difference between treatment arms in the number of patients with 'clinically significant bleeding' (reported by four out of the same five trials) or 'severe bleeding' (reported by all five trials) (respectively, RR 1.06, 95% CI 0.93 to 1.21, I² = 2%; RR 1.27, 95% CI 0.76 to 2.12, I² = 51%). We also found no evidence of a difference between treatment arms for all-cause mortality, acute transfusion reactions, adverse events, serious adverse events and red cell transfusion requirements in the trials which reported on these outcomes. No bacterial transfusion-transmitted infections occurred in the six trials that reported this outcome.Although the definition of platelet refractoriness differed between trials, the relative risk of this event was 2.74 higher following pathogen-reduced platelet transfusion (RR 2.74, 95% CI 1.84 to 4.07, I² = 0%). Participants required 7% more platelet transfusions following pathogen-reduced platelet transfusion when compared with standard platelet transfusion (MD 0.07, 95% CI 0.03 to 0.11, I² = 21%), although the interval between platelet transfusions was only shown to be significantly shorter following multiple Intercept® pathogen-reduced platelet transfusion when compared with standard platelet transfusion (MD -0.51, 95% CI -0.66 to -0.37, I² = 0%). In trials of multiple pathogen-reduced platelets, our analyses showed the one- and 24-hour count and corrected count increments to be significantly inferior to standard platelets. However, one-hour increments were similar in trials of single platelet transfusions, although the 24-hour count and corrected count increments were again significantly lower. AUTHORS' CONCLUSIONS: We found no evidence of a difference in mortality, 'clinically significant' or 'severe bleeding', transfusion reactions or adverse events between pathogen-reduced and standard platelets. For a range of laboratory outcomes the results indicated evidence of some benefits for standard platelets over pathogen-reduced platelets. These conclusions are based on data from 1422 patients included in 10 trials. Results from ongoing or new trials are required to determine if there are clinically important differences in bleeding risk between pathogen-reduced platelet transfusions and standard platelet transfusions. Given the variability in trial design, bleeding assessment and quality of outcome reporting, it is recommended that future trials apply standardised approaches to outcome assessment and follow-up, including safety reporting.